2020
DOI: 10.3390/s20164422
|View full text |Cite
|
Sign up to set email alerts
|

Mind Mapping Training’s Effects on Reading Ability: Detection Based on Eye Tracking Sensors

Abstract: As a reading comprehension strategy, mind mapping has a positive influence on the development of students’ reading ability. However, how mind mapping affects reading ability has not been well documented. In this study, we used eye tracking sensors to explore mind mapping’s effects on reading ability. The participants were foreign language learning university students in Dalian city, China. One group received foreign language reading teaching integrated with mind mapping training (experimental group), and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…48 Mind mapping which is applied in the syntactic learning model can also improve students' metacognitive skills. 49 Through mind mapping students have a higher reading level, increase reading speed to get information accurately and quickly. 50 Empirical results show that mind mapping training is an effective method for improving student's reading skills.…”
Section: Mind Mapping Compiled By Students Individuallymentioning
confidence: 99%
“…48 Mind mapping which is applied in the syntactic learning model can also improve students' metacognitive skills. 49 Through mind mapping students have a higher reading level, increase reading speed to get information accurately and quickly. 50 Empirical results show that mind mapping training is an effective method for improving student's reading skills.…”
Section: Mind Mapping Compiled By Students Individuallymentioning
confidence: 99%
“…Furthermore, the body of the talks from Tables 1 and 2 revealed that the participants have started to read and find more ideas to avoid having undeveloped presentations (Liu & Yuizono, 2020;Nikhilkumar D. Parikh, 2016). What is more, reading activity will immensely affect their vocabulary growth (Johnson & Heffernan, 2006).…”
Section: Disagreementioning
confidence: 99%
“…The sample in a study is a group of respondents who are contributors to the necessary information. Found that 9 articles involving a sampling size not exceeding 30 respondents in each group after reviewing selected studies (Ghuzayyil, 2019;Ali & Amin, 2019;Bita & Vahideh, 2020;Liu & Yuizono, 2020;Salem & Omran, 2020, Rafidah et al 2021, Pinandito et al 2021, Wafa' & Moath 2021. The sampling size between the selected studies was similar.…”
Section: Sampling Size and Focus Of Selected Studiesmentioning
confidence: 99%
“…The mind map approach was applied in an effort to improve reading ability in Japanese and English. Among them, a study conducted in China has used techniques that are quite different from other studies in the process of identifying the effectiveness of the mind map approach in Japanese reading ability (Liu & Yuizono, 2020). This study uses eye movement detectors to analyze and detect foreign language reading ability among respondents.…”
Section: Reading Abilitymentioning
confidence: 99%